2012
DOI: 10.1016/j.bbr.2011.11.042
|View full text |Cite
|
Sign up to set email alerts
|

The use of a test battery assessing affective behavior in rats: Order effects

Abstract: Many studies have used test batteries for the evaluation of affective behavior in rodents. This has the advantage that treatment effects can be examined on different aspects of the affective domain. However, the behavior in one test may affect the behavior in following test. The present study examined possible order effects in rats that were tested in three different tests: Open Field (OF), Zero Maze (ZM) and Forced Swim Test (FST). The data of the present study indicated that the behavior in ZM was the least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…It has also been suggested that C57Bl/6 mice, in contrast to other strains such as CD1 mice, are not as responsive to SSRI treatment in the FST (Petit-Demouliere et al, 2005). Another possible confounding factor may be the extensive testing battery that all animals underwent (Blokland et al, 2012). Although the order of the tests was chosen to reduce carryover effects to a minimum (McIlwain et al, 2001), it cannot be excluded that there is a test  condition interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that C57Bl/6 mice, in contrast to other strains such as CD1 mice, are not as responsive to SSRI treatment in the FST (Petit-Demouliere et al, 2005). Another possible confounding factor may be the extensive testing battery that all animals underwent (Blokland et al, 2012). Although the order of the tests was chosen to reduce carryover effects to a minimum (McIlwain et al, 2001), it cannot be excluded that there is a test  condition interaction.…”
Section: Discussionmentioning
confidence: 99%
“…20) Drug administration: Rats received intraperitoneal injection of morphine (Morphini Hydrochloridum, Alkaloid, Macedonia) (5 and 10 mg/kg, diluted in saline) 30 minutes before behavioral testing (the second testing in control and the fi rst postoperative testing in infarction group). After behavioral testing, the morphine antagonist naloxone (0.1 mg/kg, diluted in saline, Naloxon Inresa, Inresa Arzneimittel GmbH, Freiburg, Germany) was injected intraperitoneally and after 30 minutes the entire behavioral testing procedure was repeated.…”
Section: Methodsmentioning
confidence: 99%
“…However, behavior in the FST depends on its place in the order of the behavioral test battery. Rats that were tested first in the FST were less immobile and spent more time swimming than animals which received other behavioral tests on the previous day [202]. In mice, prior testing in the plus-maze did not alter immobility time in the FST [203].…”
Section: Test Design and Environmental Conditionsmentioning
confidence: 99%